(untitled) (Acta Polytechnica CTU Proceedings, 2018)
We present our custom made diffraction fitting program FitExc for the basic treatment of the 1D diffraction profiles, in particular, the Intensity(2θ) of X-ray, synchrotron or neutron diffraction measurements. In the current state, the program allows for simultaneous fitting of up to three profiles in one data set and is intended to be used mainly for precise lattice parameters determination or fitting of overlapped peaks. The entire program is built in the common MS Excel environment, it does not require any installation and is free to use.